(untitled) (Western European Journal of Medicine and Medical Science, 2024)
This article presents structural and functional changes in rats 1-3-6 months of age with EN poisoning and their detoxification with flax oil in the experiment and their changes in the histological structure, the size of the capsule wall, the thickness of the collagen fiber bundles and changes in the trabeculae in the structural -functional units.